The anti-inflammatory role of zDHHC23 through the promotion of macrophage M2 polarization and macrophage necroptosis in large yellow croaker (Larimichthys crocea) - Dai, Ting; Zhao, Ziyue; Zhu, Tingfang; Fei, Chenjie; Nie, Li; Chen, Jiong (Frontiers in Immunology, 2024)
Zinc finger Asp-His-His-Cys motif-containing (zDHHC) proteins, known for their palmitoyltransferase (PAT) activity, play crucial roles in diverse cellular processes, including immune regulation. However, their non-palmitoyltransferase immunomodulatory functions and involvement in teleost immune responses remain underexplored. In this study, we systematically characterized the zDHHC family in the large yellow croaker (Larimichthys crocea), identifying 22 members. Phylogenetic analysis unveiled that each of the 22 LczDHHCs formed distinct clusters with their orthologues from other teleost species. Furthermore, all LczDHHCs exhibited a highly conserved DHHC domain, as confirmed by tertiary structure prediction. Notably, LczDHHC23 exhibited the most pronounced upregulation following Pseudomonas plecoglossicida (P. plecoglossicida) infection of macrophage/monocyte cells (MO/MΦ). Silencing LczDHHC23 led to heightened pro-inflammatory cytokine expression and diminished anti-inflammatory cytokine levels in MO/MΦ during infection, indicating its anti-inflammatory role. Functionally, LczDHHC23 facilitated M2-type macrophage polarization, as evidenced by a significant skewing of MO/MΦ towards the pro-inflammatory M1 phenotype upon LczDHHC23 knockdown, along with the inhibition of MO/MΦ necroptosis induced by P. plecoglossicida infection. These findings highlight the non-PAT immunomodulatory function of LczDHHC23 in teleost immune regulation, broadening our understanding of zDHHC proteins in host-pathogen interactions, suggesting LczDHHC23 as a potential therapeutic target for immune modulation in aquatic species.